Integrated crop management of hot pepper (Capsicum spp.) under tropical lowland conditions: Effects of mulch on crop performance and production - Vos, J. G. M.; Sumarni, N. (Headley Brothers, 1997)
The effects of mulches were investigated within integrated crop management (ICM) of hot pepper in tropical lowland sites. Mulch materials consisted of rice straw and white or silvery plastic foils. Mulches affected soil temperature, light reflection, and soil nutrient concentrations after the last harvest. Rice straw mulch reduced soil temperature, induced faster plant growth, advanced mid-fruiting time, and resulted in higher potassium contents in leaves, but had no effect on crop producton. Plastic mulches increased soil temperature, induced faster plant growth and earlier fruiting, reduced phosphorus concentration in leaves and fruits, and increased nitrogen concentration in leaves and fruits. Yield and mean fruit weight of healthy fruits were increased and earliness of harvesting was enhanced. Improved crop performance and production with increase of fertilizer efficiency, control of evaporation, leaching and soil erosion makes plastic mulches suitable for use in ICM. To minimize the negative side-effect of plastic waste on the environment, further improvement of the mulch technology is required. Preliminary field results and a tentative cost-benefit analysis are in favour of the application of plastic mulch in hot pepper under tropical lowland conditions.